2019
DOI: 10.1111/cars.12255
|View full text |Cite
|
Sign up to set email alerts
|

Family Welfare Effort, Total Fertility, and In Vitro Fertilization: Explaining the Israeli Anomaly

Abstract: The theory of family welfare effort is a leading macro‐sociological explanation of variation in human fertility. It holds that states which provide universally available, inexpensive, high‐quality day care, generous parental leave, and flexible work schedules lower the opportunity cost of motherhood. They thus enable women, especially those in lower socioeconomic strata, to have the number of babies they want. A considerable body of research supports this theory. However, it is based almost exclusively on anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…exclusion criteria. (1) Patient with a normal response for ovarian stimulation; (2) received ovum donor for IVF ; (3) not having received a trigger for final oocyte maturation; or embryo transfer ; (4) patients with oocyte freezing cycles; (5) women in any group who aged to become eligible for another group, during the follow-up; (6) Cases with severe male factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…exclusion criteria. (1) Patient with a normal response for ovarian stimulation; (2) received ovum donor for IVF ; (3) not having received a trigger for final oocyte maturation; or embryo transfer ; (4) patients with oocyte freezing cycles; (5) women in any group who aged to become eligible for another group, during the follow-up; (6) Cases with severe male factors.…”
Section: Methodsmentioning
confidence: 99%
“…Infertility accounts for the majority of gynecological conditions worldwide, and its treatment has an overwhelmingly monetary and time concern 1,2 . These concerns resonate with couples' dire need for a child 3 .…”
mentioning
confidence: 99%
“…We suspect that this high sense of control can be explained by the fact that almost every Israeli woman who wants an abortion will probably be able to do so, since medical committees approve 99% of the requests for pregnancy termination (Israeli Ministry of Health, 2017). Furthermore, this higher sense of control might also stem from the notion that if they have future fertility problems, they will receive support from the government, as the Israeli health system provides more free fertility treatments than either Germany or Cyprus (Shenhav-Goldberg et al, 2019). The study results also indicate that the lowest sense of control was reported by Cypriot women.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that this high sense of control can be explained by the fact that almost every Israeli woman who wants an abortion is likely to be successful, since the abortion medical committees approves 99% of the requests for pregnancy termination [11]. Furthermore, this higher sense of control might also stem from the notion that if they have future fertility problems, they will receive support from the government, as the Israeli health system provides more free fertility treatments than either Germany or Cyprus [40]. We can also learn from the study results that the lowest sense of control was reported among Cypriot women.…”
Section: Discussionmentioning
confidence: 99%